The Late Babylonian Tablets in the Royal Ontario Museum - McEwan, G. J. P. (1982)
$10.00; ROMCT I will be a catalogue of the ca. 1,300 cuneiform texts in the ROM collection; the present volume is an edition of 57 economic and epistolary texts.